2020
DOI: 10.1002/joc.6667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1.5°C and 2°C of warming on regional reference evapotranspiration and drying: A case study of the Yellow River Basin, China

Abstract: Reference evapotranspiration (ETo) is one of the most important factors influencing hydrologic and climatic quantities, and increases in ETo are often considered as a primary cause for drying under global warming scenarios. Based on bias‐corrected data from the Half a degree Additional Warming, Prognosis and Projected Impacts (HAPPI) experiment, we investigated changes in ETo and drying across the Yellow River Basin (YRB) for 1.5°C and 2°C stabilized warming, relative to the current decade (2006–2015). We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Our research found that the change in the ET 0 between 1961 and 2017 had the greatest positive correlation with Tmean, followed by U 2 and SD. Jian et al similarly found an increase in the ET 0 , due to temperature changes [74]. Chen et al and Xie and Zhu concurred that wind speed has an important influence on the ET 0 of the TP [75,76].…”
Section: The Linkages Of Et 0 With Other Factorsmentioning
confidence: 89%
“…Our research found that the change in the ET 0 between 1961 and 2017 had the greatest positive correlation with Tmean, followed by U 2 and SD. Jian et al similarly found an increase in the ET 0 , due to temperature changes [74]. Chen et al and Xie and Zhu concurred that wind speed has an important influence on the ET 0 of the TP [75,76].…”
Section: The Linkages Of Et 0 With Other Factorsmentioning
confidence: 89%
“…The regional warming in China, especially over drylands (Huang et al ., 2017), has a rate that is much faster than the global mean air temperature (see Figure S2; Sun et al, 2019). In addition, the significant increase of maximum air temperature is suggested to make the largest contribution to the increase of PET, for example, over the Yellow River basin (Jian et al ., 2020). Therefore, the high SNR of PET change in China may be attributed to the high SNR of air temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Observed and projected PET based on Equation () were obtained from Jian et al . (2020), in which detailed calculation process was introduced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations